Ecotourism in the Flint Hills: exploring design and programming opportunities for Prairiewood in Manhattan, Kansas - Franks, Elizabeth (Kansas State University, 2022)
Many visitors traveling through the Flint Hills do not know its history or appreciate the significance of this threatened ecoregion. While the concept of ecotourism and its impacts have been explored in the literature, there has been less attention paid towards integrating specific programming elements found within ecotourism types and how they help promote a stronger human-nature connection. This Master’s project and report provides Prairiewood owners and staff with several possible design scenarios aimed at expanding and promoting Prairiewood as a leading example of how ecotourism could be better supported in the Flint Hills. More specifically, this project and report identifies various environmental, cultural, historical, and aesthetic cues that are associated with the Flint Hills ecoregion. Further, this report explores ways to allow visitors to experience these cues first-hand, both at Prairiewood and more distant locations within the Flint Hills. Through a precedent analysis of specific ecotourist locations and interviews with educational staff at various facilities within the Flint Hills, a better understanding of how successful and beneficial ecotourist programming aimed at promoting better human nature connections was developed. These programming elements and identified Flint Hills’ characteristic cues contributed to a projective design outcome for this project, which includes educational, environmental, and recreational considerations. These findings offer more insight into how to successfully promote ecotourism in the Flint Hills ecoregion and could find connections back to the existing body of literature about ecotourism.
Keywords: Ecotourism; Nature-base tourism; Flint Hills ecoregion